Speciation of inorganic arsenic in particulate matter by combining HPLC/ICP-MS and XANES analyses. Issue 10 (23rd October 2015) - Tirez, K.; Vanhoof, C.; Peters, J.; Geerts, L.; Bleux, N.; Adriaenssens, E.; Roekens, E.; Smolek, S.; Maderitsch, A.; Steininger, R.; Göttlicher, J.; Meirer, F.; et al.
<x xml:space="preserve">Abstract</x> Inorganic arsenic species in ambient particulate matter (PM10 and PM2.5) have been determined in an urban area, in the vicinity of a metallurgical industrial plant.